Online Moodle Sebagai E-Learning Bagi Siswa SMK Peserta Praktek Kerja Industri - Mubarrak, Akbar; Ikhsan, Jaslin (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
This study aims to integrate ICT by designing and applying online moodle as an e-learning material for class XII TKR.B students of SMK Negeri 1 Purworejo who undergo On Job Training for three months. In developing the e-learning, researchers use Research and Development method and ADDIE instructional design. Result of this study is the design and implementation of moodle as online learning media for OJT students. Teachers can upload learning modules and provide a test to determine the extent of students' understanding of material provided by the module. Online moodle can be accessed by students anytime and anywhere, either from mobile phone or internet cafes. All facilities provided in online moodle can easily be used as a medium of distance learning.